Economics of Using Cocoa Bean Shell as Feed Supplement for Rabbits - Ayinde, O.E.; Ojo, V.; Adeyina, A.A.; Adesoye, O. (Pakistan Journal of Nutrition, 2010)
The study analyzed the economics of using cocoa bean shell (cbs) as feed supplement in rabbit production. Data used for this study was collected from an experimental study of performance of rabbits fed graded levels of various treatments of CBS as feed supplement. Gross margin and dominance analysis were used to analyze the data. The study showed that untreated CBS can be used economically at 100g/kg inclusion in rabbit feed while hot Water treated CBS (WCBS) can be included up to 200 g/kg in rabbit feed. The study recommends the use of hot water treatment of CBS at 200 g/kg inclusion for optimum profitability of rabbit production.